MODEL PEMBELAJARAN ELEMEN INKUIRI DALAM PENINGKATAN KOMPETENSI MENULIS KARYA ILMIAH SISWA KELAS XI SMA NEGERI 9 SEMARANG - Yuniawan, Tommi; Wardani, Endah Dyah (Lembaran Ilmu Kependidikan, 2008)
This research has a purpose to describe the improvement of the competence inwriting scientific papers of grade XI-IA of SMA Negeri 9 Semarang by using inquiryelement. This research is a classroom action research by using Kemmis and Taggart’scycle theory. There are 2 cycles that consist of 4 steps each: planning, observing,action and reflection. The subject is the skill in writing scientific papers. The resultvariable of this research is the competence of scientific papers writing and the processvariable is the inquiry element. This research uses some test instruments, i.e. 1) thesystem of writing; 2) the ability to think logically; 3) the coherence between the titleand the content; 4) the ability to use proper Indonesian spelling; 5) the ability to writeparagraphs, sentences and words; 6) the ability to write quotations; 7) the ability towrite the bibliography ; and 8) the order of the writing. The non-test instruments arein the form of 1) observation sheet; 2) students’ journal; and 3) interview. The testdata were analyzed quantitatively using statistical formula. Categorization anddescription were used to analyze the non-test data. The result shows that the inquiryelement can be used in teaching the scientific paper writing of grade XI-IA students ofSMA Negeri 9 Semarang. The improvement of the competence can be seen in cycle Iand II. The average score of pre-cycle step was 62.11. It increased up to 69.55 in cycleI and reached 77.10 in cycle II.Kata kunci: elemen inkuiri, karya ilmiah, kompetensi menulis, penelitian tindakankelas